Client perceptions of a work rehabilitation programme for women: The Redesigning Daily Occupations (ReDO) project. (March 2013) - Wästberg, Birgitta A.; Erlandsson, Lena-karin; Eklund, Mona
Abstract Aim: The Redesigning Daily Occupations programme (ReDO) is a Swedish work rehabilitation programme for women on sick leave due to stress-related disorders. The aim of the study was to investigate the participants' perceptions of taking part in the work rehabilitation programme. Methods: Seven of the 38 women who completed ReDO were interviewed during and after the programme. The interviews were analysed by manifest and latent content analysis. Results: The informants were satisfied with the content of the programme and the support they received in the programme and when returning to work. The women thought they had become more aware of what they did during a day and how they performed their daily activities, which helped them to change their ways of performing them. The result highlighted different parts of their rehabilitation process which constituted four sub-themes: "Perceptions of the ReDO", "The intrinsic process", "Person-related changes", and "Perceptions of returning to work", and formed the core theme "Critical parts of the rehabilitation process". Conclusions: The findings may not be generalized to other settings and future research should further investigate work rehabilitation for the target group.